(untitled) (Applied Biological Research, 2023)
Non-communicable diseases (NCD) are common global public health issues and among all the NCDs, cardiovascular diseases, Ischemic heart disease, cardiac anxiety, depression, and stress are major health problems. This study was aimed to identify the cardiac anxiety, depression, and stress among the patients with myocardial infarction (MI). A cross-sectional study was chosen to measure cardiac anxiety, depression, and stress among the patients with coronaryartery disease admitted to the coronary care department of a tertiary care hospital in Bhubaneswar, India. The purposive sampling method included the study samples. Among the 111 participants, the majority after the acute event of MI had extremely severe depression (35.1%) and moderate levels of stress (27.9%). Anterior wall myocardial infarction and inferior wall myocardial infarction (28.8% each) were more prevalent type of MI among the participants. The mean value of cardiac anxiety was 39.83 (9.01), 24.38 (7.2) for depression, and 23.93 (8.1) for stress. Hence psychiatric morbidity assessment is critical among patients with myocardial infarction and should pan to provide need-based intervention to reduce further mortality and for a speedy recovery rate.